Diarrhea in suckling lambs is associated with changes in gut microbiota, serum immunological and biochemical parameters in an intensive production system - Tao Zhong; Yaxuan Wang; Xinlu Wang; Aline Freitas-de-Melo; Hua Li; Siyuan Zhan; Linjie Wang; Jiaxue Cao; Dinghui Dai; Jiazhong Guo; Li Li; Hongping Zhang; et al. (Frontiers in Microbiology, 2022)
The incidence of diarrhea in lambs is frequent in large-scale sheep farms, which greatly impacts the growth and health of lambs. The aim of this study was to assess the changes in serum biochemical and immunological parameters and gut microbiome composition in suckling lambs suffering from diarrhea or not, reared on an intensive commercial farm. We found a reduced diversity of intestinal bacteria in suckling lambs suffering from diarrhea. Firmicutes and Bacteroidetes were the dominant flora in both groups of lambs, while the Bacteroidetes decreased in diarrheic lambs, no changes were reported in Firmicutes. Compared with healthy lambs, the proportion of aerobic bacteria, facultative anaerobic bacteria, and stress tolerant bacteria increased in lambs suffering from diarrhea, while that of anaerobic bacteria and potentially pathogenic bacteria decreased slightly. In addition, the contents of total cholesterol, immunoglobulins (Ig) G, and IgM in the serum of lambs suffering from diarrhea were lower than those of healthy lambs. This study explored the association between diarrhea occurrence, intestinal microbial community structure, and metabolic and immunological status in Hu lambs.